PENGARUH PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK NARAPIDANA LEMBAGA PEMASYARAKATAN KELAS 1 CIREBON (PAS MART) - Giyats Rif’at Afifi (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
This study aims to determine the relationship conditions of sales promotions and purchasing decisions in Class I Correctional Institutions Cirebon (Pas Mart), besides that this study also aims to determine how much influence the sales promotion on purchasing decisions in Class I Correctional Facilities Cirebon (Pas Mart). This type of research is a descriptive study with a quantitative approach. The population used in this study were all consumers who had shopped at the Cirebon Class I Correctional Institution (Pas Mart), a sample size of 51 respondents, sampling using accidental sampling techniques. Data obtained through the distribution of questionnaires that have been tested both validity and reliability tests. The data analysis technique uses simple regression analysis. Data is processed through Statistical Product and Service Solution (SPSS) Version 23. The results of this research have shown that there is a positive relationship between sales promotions with purchasing decisions and there is an influence of sales promotions on purchasing decisions.